Comparative metagenomics reveals different hydrocarbon degradative abilities from enriched oil-drilling waste. (October 2018) - Napp, Amanda P.; Pereira, José Evandro S.; Oliveira, Jorge S.; Silva-Portela, Rita C.B.; Agnez-Lima, Lucymara F.; Peralba, Maria C.R.; Bento, Fátima M.; Passaglia, Luciane M.P.; Thompson, Claudia E.; Vainstein, Marilene H.
Abstract: The oil drilling process generates large volumes of waste with inadequate treatments. Here, oil drilling waste (ODW) microbial communities demonstrate different hydrocarbon degradative abilities when exposed to distinct nutrient enrichments as revealed by comparative metagenomics. The ODW was enriched in Luria Broth (LBE) and Potato Dextrose (PDE) media to examine the structure and functional variations of microbial consortia. Two metagenomes were sequenced on Ion Torrent platform and analyzed using MG-RAST. The STAMP software was used to analyze statistically significant differences amongst different attributes of metagenomes. The microbial diversity presented in the different enrichments was distinct and heterogeneous. The metabolic pathways and enzymes were mainly related to the aerobic hydrocarbons degradation. Moreover, our results showed efficient biodegradation after 15 days of treatment for aliphatic hydrocarbons (C8-C33) and polycyclic aromatic hydrocarbons (PAHs), with a total of about 50.5% and 46.4% for LBE and 44.6% and 37.9% for PDE, respectively. The results obtained suggest the idea that the enzymatic apparatus have the potential to degrade petroleum compounds. Highlights: The study reports comparative metagenomics of distinct oil drilling waste-enriched samples. It comparatively evaluates the phylogenetic and functional diversity of two different oil drilling waste-enriched consortia. The sequences and metabolic pathways involved in oil degradation have been reported. The degradation treatments were satisfactory for a broad range of petroleum hydrocarbons.